Pengaruh Work-life Balance dan Disiplin Kerja terhadap Loyalitas Guru di Sekolah Dasar Negeri di Kecamatan Samarinda Kota - Sheila Salsabila; Praja Hadi Saputra; Yulia Tri Kusumawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of work-life balance and work discipline on the loyalty of elementary school teachers in Samarinda City District. To achieve this goal, this study uses a quantitative approach involving 93 responded as a samples. Data collection techniques are carried out through observation, as well as distributing questionnaires to teachers. The data collected were analyzed using descriptive statistics. The results of the studies indicate that work-life balance and work discipline have a positive influence on the loyalty of elementary school teachers in Samarinda City District.